Beiträge zur Insektenfauna der DDR: Lepidoptera - Arctiidae, Nolidae, Ctenuchidae, Drepanidae, Cossidae und Hepialidae. - Schmidt, Peter (Contributions to Entomology = Beiträge zur Entomologie, 1991)
In this contribution 42 species of Arctiidae, 7 species of Nolidae, 2 species of Ctenuchidae, 7 species of Drepanidae, 4 species of Cossidae and 5 species of Hepialidae are faunistically evaluated for the territory of the GDR. About 9.000 data of finds by collectors and about 3.000 entries from available literature provide a relatively good survey of the distribution of the species. As far as possible, the distribution of the species in Europe and in their entire area is shown. Flying periods and possible borders of their areas are indicated. Interested readers are offered information about the degrees to which species are endangered and about taxonomical questions, derived from the study of recent literature.